The regulation of calbindin D-28K by epidermal growth factor in MDBK cells and the involvement of signal transduction pathways. - Donepudi, Manjula. (University of Ottawa (Canada), 1996)
We investigated the ability of 1,25(OH)$\rm\sb2D\sb3$ and EGF to modulate cell proliferation and VDR levels in renal distal tubular cells. As well, we characterized the effects of EGF on the vitamin D-dependent calcium binding protein calbindin D-28K in order to determine if changes in its expression were linked to cell proliferation. The MDBK cells represent an ideal in vitro system for studying the regulation of calbindin D-28K and VDR since both proteins are expressed in a 1,25(OH)$\rm\sb2D\sb3$-dependent manner in these cells. Assessment of DNA synthesis, cell cycle kinetics and cell number indicated that EGF significantly increased DNA synthesis (40%), cell number and the population of cells in S phase of the cell cycle compared to vehicle treated MDBK cells. On the other hand, 1,25(OH)$\rm\sb2D\sb3$ did not affect proliferation ot MDBK cells nor did it blunt the mitogenic actions of EGF in these cells. We observed that EGF down-regulated 1,25(OH)$\rm\sb2D\sb3$-binding levels (33%) after 4 hour and 24 hour treatment compared to PBS treatment for the same time. Pre-treatment with 1,25(OH)$\rm\sb2D\sb3,$ prior to the addition of EGF, restored VDR binding to levels observed when cells were exposed to 1,25(OH)$\rm\sb2D\sb3$ alone. The changes in 1,25(OH)$\rm\sb2D\sb3$ binding in response to EGF prompted us to examine EGF effects on calbindin D-28K expression. MDBK cells were stimulated with EGF for up to 24 hours and calbindin D-28K levels were assessed by ELISA and immunoblotting. After 24 hours with EGF calbindin D-28K was down-regulated compared to control treated cells. Calbindin D-28K down-regulation was prevented by 1,25(OH)$\rm\sb2D\sb3$ and therefore correlated with the changes in VDR binding observed under the same conditions. However, acute (4 hour) EGF treatment up-regulated calbindin D-28K protein levels as assessed by ELISA and immunoblotting. (Abstract shortened by UMI.)
Keywords: Biology, Cell.